PELAYANAN SOSIAL LANJUT USIA (STUDI KASUS PADA ENAM ORANG WARGA BINAAN SOSIAL di UPT PELAYANAN SOSIAL TUNA RUNGU WICARA DAN LANJUT USIA PEMATANG SIANTAR) - Nesry Oderista Damanik (Welfare StatE, 2013)
Over time, many changing situations. Similarly, the life expectancy is increasing. Increasing elderly population is not only a phenomenon in Indonesia but also has globally.In 2000 the elderly population worldwide is estimated as many as 426 million or approximately 6.8%. This amount will increase by almost double by 2025, ie to about 828 million people, or about 9.7% of the total world population. In Indonesia in 2000 estimated 7.4% of Indonesia's population, or about 15.3 million people will be aged over 60 years. Central Statistics Agency (BPS, 2004) concluded that the 21st century is a century older Indonesia (era of population aging), due to the growth of the elderly population in Indonesia is expected to be faster than the other countries. Changes in the composition of the elderly population raises new needs that must be met are different from the needs of other age groups, so it can also be a complex issue for the elderly, both as individuals, families and communities. This study aims to look at how the social services provided UPT Pelayanan Sosial Tuna Rungu Wicara dan Lanjut Usia Pematang Siantar against social inmates elderly. This is a descriptive study with a qualitative approach that aims to provide a picture of how the social services provided to the elderly social prisoners. The unit of analysis in this study were six peoples socially elderly inmates in UPT Pelayanan Sosial Tuna Rungu Wicara dan Lanjut Usia Pematang Siantar. The data collection technique used is the study of literature, direct observation and interviews. The Results of data analysis showed that the elderly social services provided UPT Pelayanan Sosial Tuna Rungu Wicara dan Lanjut Usia Pematang Siantar performing well, looks with satisfaction of service perceived by six peoples socially elderly inmates although there are still some things that need to be addressed in order to improve quality of service. Keywords: Social Services, Elderly.